2009
DOI: 10.1112/jlms/jdp044
|View full text |Cite
|
Sign up to set email alerts
|

On local geometry of non-holonomic rank 2 distributions

Abstract: Abstract. In 1910 E. Cartan constructed a canonical frame and found the most symmetric case for maximally nonholonomic rank 2 distributions in R 5 . We solve the analogous problem for germs of generic rank 2 distributions in R n for n > 5. We use a completely different approach based on the symplectification of the problem. The main idea is to consider a special odd-dimensional submanifold WD of the cotangent bundle associated with any rank 2 distribution D. It is naturally foliated by characteristic curves, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 15 publications
1
55
0
Order By: Relevance
“…It is shown also that similar double fibrations exist for rank 2 distributions on manifolds of dimension n ≥ 5 and also for distributions of higher rank in [8] [9] implicitly and in [10] explicitly.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is shown also that similar double fibrations exist for rank 2 distributions on manifolds of dimension n ≥ 5 and also for distributions of higher rank in [8] [9] implicitly and in [10] explicitly.…”
Section: Introductionmentioning
confidence: 89%
“…Note that, moreover in [8] [9], it is shown that cone structures exist for rank 2 distributions on n-dimensional manifolds for arbitrary n ≥ 5, and the cone structures were extensively used for constructions of the structures of absolute parallelism and invariants of such distributions. It is shown also that similar double fibrations exist for rank 2 distributions on manifolds of dimension n ≥ 5 and also for distributions of higher rank in [8] [9] implicitly and in [10] explicitly.…”
Section: Introductionmentioning
confidence: 99%
“…On the other extreme, a rank two distribution is called generic, or (2,3,5), as e.g. in [6,7], if we have:…”
Section: Cartan's Invariants Of Rank Two Distributions In Dimension Fivementioning
confidence: 99%
“…They look ugly, and they all involve the derivatives of the function ρ up to the sixth order. We treated these equations as algebraic equations for ρ (6) , ρ (5) and ρ (4) , and used the same trick as in the proof of Theorem 4.2. Namely, we algebraically solved equation for ρ (4) , differentiated it, and compared it with the ρ (5) obtained algebraically.…”
Section: Surface With One Killing Vector and A Surface Of Constant Cumentioning
confidence: 99%
See 1 more Smart Citation